ROLE OF PRODUCTIVE ZAKAT FUNDS ON MUSTAHIK MICRO BUSINESS DEVELOPMENT (Case Study of Medan City Rumah Zakat) - Nur Hadiati Putri Sinaga, Sri Rezeki; Adilla, Nur; Sriani, Sulastri (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2020)
Zakat is one of the commands of the Islamic religion which is considered worship or good deeds that can give effect to others. As one form of compulsory worship, the order to pay zakat also has an important role in building economic development. Economic development can be built through the use of productive zakat to empower mustahik in the micro business sector. This effort is expected to make Mustahik somewhat independent in the economic field. However, in the implementation there were still some obstacles encountered to develop this micro business. One of them is lack of capital and lack of guidance regarding the business they are involved in. This research method uses descriptive method to find out the collection, management and empowerment of zakat fund system of Rumah Zakat Medan. To analyze the effects of zakat funds, productive capital, turnover, and profit / income from operations using different testing methods (Paired T-test). Objects in this study were given mustahik capital assistance by Zakat of 35 respondents. From the results of the study showed that an increase in mustahik income after getting capital assistance. This increase in business income shows the development of micro mustahik businesses which are also inseparable from the adnaya of assistance that is carried out regularly by Rumah Zakat.